The Influence of GDP and Interest Rate on the Return on Assets of Sharia Life Insurance Companies in Indonesia During the COVID-19 Pandemic - Donafeby Widyani (Research Synergy Foundation, 2023)
This paper examines the relationship between the effect of GDP and Interest Rate on the Return on Assets of Islamic insurance companies in Indonesia during the COVID-19 pandemic, using the period 2020 to 2022. Multiple linear regression is used to test the degree of relationship between macroeconomic factors and company performance. The results of the study show that GDP and Interest Rate have no significant effect on the ROA of Islamic life insurance companies in Indonesia. There are three reasons provided, the sharia insurance industry has different characteristics from other industries, the social behavior factor during the COVID-19 pandemic, and there are also other factors that affect the ROA of sharia insurance companies. The findings contribute to the operation of Islamic insurance in Indonesia for regulators, investors, and policyholders.